(434) Development Planning: The Sector phase, with Different Gestation Periods التخطيط التنموي: المرحلة القطاعية بفترات نضوج مختلفة - Tinbergen, J. (معهد التخطيط القومى, 2024)
This study examines development planning from a sectoral perspective with particular emphasis on differences in gestation periods among economic sectors and investment projects and their implications for long-term economic planning. The research is based on the assumption that economic sectors do not respond uniformly to investment activities since the time required to transform investments into productive capacity differs significantly across sectors. Consequently, these differences create important challenges for planning authorities in designing development strategies and allocating resources efficiently. The study adopted a quantitative and analytical approach based on economic planning models linking inputs and outputs across sectors. It investigated the interrelationships among sectors using technical coefficients that describe patterns of economic interdependence. The research also introduced a distinction between national sectors and international sectors, identifying sectors whose outputs mainly satisfy domestic demand and those capable of interacting with international markets through exports and imports. Furthermore, the study analyzed the role of sectoral investments in achieving economic growth objectives and emphasized that the effectiveness of development plans depends largely on determining the optimal distribution of investments among different sectors. Particular attention was given to sectors such as construction, energy, transportation, and public services because of their strategic contribution to broader economic activity and their influence on production capacity across the economy. The findings indicate that effective economic planning requires careful consideration of time differences among projects regarding implementation periods and expected returns. Ignoring these temporal dimensions may create structural imbalances and inefficient resource allocation. The study concludes that dynamic planning models capable of incorporating time factors into economic analysis provide an effective framework for improving investment decisions and promoting balanced and sustainable economic development.